MASJID DAN FUNGSI SOSIAL KEMANUSIAAN: (Mosques and Social Functions of Humanity) - Baeti Rohman (Raqib: Jurnal Studi Islam, 2025)
The presence of a mosque has a vital function in the lives of Muslims. In a narrow understanding, mosques are often reduced to merely being a place of prayer, in principle this understanding is not wrong to a certain extent, but along with the development of the times, mosques are multi-functional, not only acting as a place of prayer but other types of worship are also routinely held in mosques ranging from dhikr, prayer, to tadarus Al-Quran. On a broader scale, mosques also have a social humanitarian function that is not only related to natural disasters, in normal situations the social humanitarian function of mosques continues to run. The social humanitarian function related to disasters, for example, by making mosques a temporary shelter for disaster victims. Meanwhile, blood donation activities, sharing basic necessities, health checks and others are social humanitarian functions carried out by mosques in normal times. The social humanitarian function carried out by mosques indicates that mosques have become one with the lives of the people, mosques take on a greater role in society.